Analisis Marketing Public Relations pada Serial Netflix Squid Game Season 2 - Yunita Indinabila; E.Rizky Wulandari; Yuga Adi Kusuma (LPPM Stikosa-AWS, 2025)
This article discusses the public relations marketing strategies employed by Netflix in promoting Squid Game Season 2. With the increasing competition in the entertainment industry, Netflix has adopted innovative approaches to capture audience attention and foster deeper engagement. This research analyzes various elements of the marketing strategy, including the use of social media, collaborations with influencers, and the organization of interactive events that involve fans. Through qualitative methods, this article explores the impact of these strategies on the popularity of the series, as reflected in viewership numbers and interactions on digital platforms. The analysis results indicate that an integrated and responsive approach to pop culture trends has significantly contributed to the success of Squid Game Season 2. These findings provide valuable insights for marketing practitioners and academics regarding the importance of innovation in public relations strategies in the digital age.